When a parabola opens up/down, its vertex form equation is
y = a(x - h)2 + k
where (h, k) is the vertex.
a < 0 ----> parabola opens down
a > 0 ----> parabola opens up
Write the following equations of the parabolas in vertex form :
Example 1 :
y = x2 - 2x - 5
Solution :
y = x2 - 2x - 5
y = x2 - 2(x)(1) + 12 - 12 - 5
Using the identity (a - b)2 = a2 - 2ab + b2,
y = (x - 1)2 - 12 - 5
y = (x - 1)2 - 1 - 5
y = (x - 1)2 - 6
Example 2 :
y = -x2 - 14x - 59
Solution :
y = -x2 - 14x - 59
y = -1(x2 + 14x) - 59
y = -1[x2 + 2(x)(7) + 72 - 72] - 59
Using the identity (a + b)2 = a2 + 2ab + b2,
y = -1[(x + 7)2 - 72] - 59
y = -1[(x + 7)2 - 49] - 59
y = -1(x + 7)2 + 49 - 59
y = -1(x + 7)2 - 10
Example 3 :
y = x2 + 4x
Solution :
y = x2 + 4x
y = x2 + 2(x)(2) + 22 - 22
Using the identity (a + b)2 = a2 + 2ab + b2,
y = (x + 2)2 - 22
y = (x + 2)2 - 4
Example 4 :
y = 2(x - 5)(x - 3)
Solution :
y = 2(x - 5)(x - 3)
y = 2(x2 - 3x - 5x + 15)
y = 2(x2 - 8x + 15)
y = 2x2 - 16x + 30
y = 2(x2 - 8x) + 30
y = 2[x2 - 2(x)(4)] + 30
y = 2[x2 - 2(x)(4) + 42 - 42) + 30
Using the identity (a + b)2 = a2 + 2ab + b2,
y = 2[(x - 4)2 - 42] + 30
y = 2[(x - 4)2 - 16] + 30
y = 2[(x - 4)2 - 32 + 30
y = 2(x - 4)2 - 2
When a parabola opens to the left or right, its vertex form equation is
x = a(y - k)2 + h
where (h, k) is the vertex.
a < 0 ----> parabola opens to the left
a > 0 ----> parabola opens up to the right
Write the following equations of the parabolas in vertex form :
Example 5 :
x = y2 - 2y - 5
Solution :
x = y2 - 2y - 5
x = y2 - 2(y)(1) + 12 - 12 - 5
Using the identity (a - b)2 = a2 - 2ab + b2,
x = (y - 1)2 - 12 - 5
x = (y - 1)2 - 1 - 5
x = (y - 1)2 - 6
Example 6 :
x = -y2 - 14y - 59
Solution :
x = -y2 - 14y - 59
x = -1(y2 + 14y) - 59
x = -1[y2 + 2(y)(7) + 72 - 72] - 59
Using the identity (a + b)2 = a2 + 2ab + b2,
x = -1[(y + 7)2 - 72] - 59
x = -1[(y + 7)2 - 49] - 59
x = -1(y + 7)2 + 49 - 59
x = -1(y + 7)2 - 10
Example 7 :
x = y2 + 4y
Solution :
x = y2 + 4y
x = y2 + 2(y)(2) + 22 - 22
Using the identity (a + b)2 = a2 + 2ab + b2,
x = (y + 2)2 - 22
x = (y + 2)2 - 4
Example 8 :
x = -3(y - 2)(y + 8)
Solution :
x = -3(y - 2)(y + 8)
x = -3(y2 + 8y - 2y - 16)
x = -3(y2 + 6y - 16)
x = -3y2 - 18y + 48
x = -3(y2 + 6y) + 48
x = -3[y2 + 2(y)(3)] + 48
x = -3[y2 + 2(y)(3) + 32 - 32] + 48
Using the identity (a + b)2 = a2 + 2ab + b2,
x = -3[(y + 3)2 - 32] + 48
x = -3[(y + 3)2 - 9] + 48
x = -3(y + 3)2 + 27 + 48
x = -3(y + 3)2 + 75
Kindly mail your feedback to v4formath@gmail.com
We always appreciate your feedback.
©All rights reserved. onlinemath4all.com
Feb 06, 25 07:42 PM
Feb 06, 25 06:10 PM
Feb 06, 25 09:46 AM